Investigation of alder (Alnus incana) chloroplast ribosomal RNA genes. - Lévesque, Madeleine. (University of Ottawa (Canada), 1990)
In an effort to position the alder, Alnus incana, in the scope of phylogenetic relationships, ribosomal RNA genes from its chloroplasts have been cloned and analysed. A genomic library was constructed in the vector LambdaGEM-11 with DNA isolated from leaf tissue. DNA fragments covering the length of the 23S and 16S rRNA genes as well as trnI and sections of trnA were sequenced. The order of chloroplast genes within the sequenced region of alder is identical to that seen in higher plants: 16S-trnI-trnA-23S. Comparisons of the primary sequence of the alder 16S and 23S rRNA genes with available ribosomal RNA and DNA sequences have demonstrated the greatest degree of homology between the alder sequences and those of other higher plant sequences. Comparisons to bacterial sequences yield higher homologies to the cyanobacterial sequences as opposed to those of E. coli. Further sequence analysis shows that the primary sequence obtained for the 16S rRNA gene in alder can be folded to follow the secondary structure of the maize 16S rRNA molecule. (Abstract shortened by UMI.)
Keywords: Biology, Genetics.